Antipsychotic-associated neuroleptic malignant syndrome (NMS) in schizophrenia patients: a narrative review - Puspita, Okta; Bambang Hastha Yoga; Zullies Ikawati (Indonesian Journal of Pharmacology and Therapy, 2024)
Neuroleptic malignant syndrome (NMS) is a neurological disorder with an high mortality rate among schizophrenia patients who receive antipsychotics as the primary long-term therapy. Appropriate selection of antipsychotics in NMS should be carefully considered to obtain maximal effectiveness with minimal side effects. An evaluation of the safety profile of the antipsychotics is important due to their different treatment patterns and rapid onset of symptoms. This review article aimed to compare the safety profile of antipsychotics in relation to NMS in schizophrenia patients. It was a narrative review using multiple search engines included PubMed, Google Scholar, and Springer to collect publications from 2007 to 2023. Of the total 14 articles reviewed, 7 articles explained the role of antipsychotics in NMS, 5 articles about the onset of NMS, and 7 articles about mortality rate. The incidence of NMS was less then 0.11%, typical antipsychotics were the most common cause of NMS, especially high-potency antipsychotics compared with atypical antipsychotics. Meanwhile, the onset of NMS consistently occured within 30 d of antipsychotic initiation with a symptom duration of 1 to 30 d, and the mortality rate was also higher for typical antipsychotics. In conclusion, the choice of antipsychotics must be carefully considered and its use must be monitored due to the rapid onset and high mortality. The use of antipsychotics is not free from the risk of NMS. The heterogeneous symptoms of NMS require earlier detection to reduce disease progression.